2017
DOI: 10.4103/0971-4065.202830
|View full text |Cite
|
Sign up to set email alerts
|

Impact of malnutrition, inflammation, and atherosclerosis on the outcome in hemodialysis patients

Abstract: Malnutrition, inflammation, and atherosclerosis are significant problems in patients on hemodialysis. A prospective, observational study in 100 hemodialysis patients for 2 years was conducted. The primary outcomes were hospitalizations and mortality at the end of 2 years. The mean age was 61 ± 11.3 years and 69% were male. Seven patients did not complete the study (five underwent transplant and two were shifted to other units). Serum albumin was significantly lower in malnourished patients at 6 months from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 32 publications
1
14
0
1
Order By: Relevance
“…The namesake components of the MIA syndrome have been known for decades as predictors of a short life expectancy for the MHD patients [24]. Indeed, the mortality rate within 2 years in an Indian MHD cohort was 0, 8.7, 13.0 and 45.0% when none, one, two and three of these components were present, respectively [25]. In general agreement, we found that the pre-dialysis Scr, hs-CRP and pre-dialysis SBP were significant determinants of all-cause mortality as each may serve as a surrogate marker for the individual component of the MIA syndrome [26].…”
Section: Discussionmentioning
confidence: 99%
“…The namesake components of the MIA syndrome have been known for decades as predictors of a short life expectancy for the MHD patients [24]. Indeed, the mortality rate within 2 years in an Indian MHD cohort was 0, 8.7, 13.0 and 45.0% when none, one, two and three of these components were present, respectively [25]. In general agreement, we found that the pre-dialysis Scr, hs-CRP and pre-dialysis SBP were significant determinants of all-cause mortality as each may serve as a surrogate marker for the individual component of the MIA syndrome [26].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the studied tool was found to correlate with anthropometric measures and biochemical measures in a variety of patient populations in Asia and Europe [ 45 , 64 ]. Moreover, SGA with category B or C predicts longer hospital stays [ 45 ] and mortality [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we conducted the assessment of the relationship between the nutritional status and muscle strength in patients undergoing HD; according to SGA, 73.3% of patients were well-nourished and 26.7% of patients were moderately malnourished. According to Kirushnan et al, among 93 HD patients who participated in the study, 68% of patients were well-nourished and 32% of patients were undernourished (there were 29% of moderate and 3% of severe malnutrition cases) [13]. Koor et al found that in a study that included 190 HD patients, according to SGA, 8.4% of patients were well-nourished, 47.4% of patients were mildly malnourished and 44.2% of patients were moderately malnourished [14].…”
Section: Discussionmentioning
confidence: 99%